Production and Thermal-Structural Characterization of Nano-Oxide-Doped Paraffin-Based Phase Change Composite Materials for Thermal Storage Applications - Yucel, Halit Lutfi; Ozdemir, Osman; Kahraman, Gokhan (Springer, 2026)
Paraffin-based composite phase change materials (PCMs) have been synthesized for thermal energy storage applications to enhance thermal conductivity and stability while maintaining latent heat storage capacity. In this study, RT42 paraffin was modified with inorganic nano-oxides (Al2O3, CuO, SiO2, and ZnO) in the presence of sodium dodecyl sulfate (SDS) as a surfactant. The incorporation of SDS improved nanoparticle dispersion and reduced agglomeration, resulting in enhanced phase-change behavior and improved structural homogeneity. Differential scanning calorimetry (DSC) analysis revealed slight variations in melting and crystallization temperatures, while the ZnO-doped composite retained up to 92% of the latent heat storage capacity of pure RT42. Among all the investigated composites, the Al2O3-doped sample exhibited the highest thermal conductivity and specific heat capacity. Thermogravimetric analysis (TGA) indicated an increase of approximately 15-20 degrees C in the decomposition temperature, demonstrating enhanced thermal stability. X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses confirmed the preservation of the crystalline structure and improved microstructural uniformity. The developed SDS-assisted nano-oxide/RT42 composites exhibit significant potential for passive thermal regulation in renewable energy and building applications.
Keywords: Energy-Storage